THE EFFECT OF PROLONGED CULTIVATION IN VITRO UPON THE PATHOGENICITY OF YELLOW FEVER VIRUS - Theiler, Max (The Rockefeller University Press, 1937)
1. Experimental evidence is presented to show that prolonged cultivation of yellow fever virus in vitro results in a change in its pathogenicity, and that this change varies with the type of tissues used for the cultivation. 2. In the tissue cultures used for the propagation of the virus, three different types of tissues were used. They included whole mouse embryo, chick embryo from which the head and spinal cord had been removed, and testicular tissues of mice and guinea pigs. 3. The changes in the pathogenicity of the virus cultivated for a period of over 3 years in a medium containing the tissues of whole mouse embryo were not striking. The viscerotropic virulence of the virus appeared somewhat diminished, in that when injected subcutaneously into rhesus monkeys or hedgehogs it failed to produce a fatal infection, although there is evidence to indicate that a generalized infection takes place as demonstrated by the appearance of virus in the circulating blood in relatively high concentration during infection. The neurotropic virulence of the virus remained unaltered during the cultivation in this medium. 4. The changes in the pathogenicity of the virus cultivated in medium containing tissues of chick embryo from which the head and spinal cord had been removed were very pronounced. The viscerotropic virulence of the virus was lost to a large extent. When injected subcutaneously into monkeys there was as a rule a very mild generalized infection, as demonstrated by the minimal quantities of virus found in the circulating blood. Its neurotropism was also much diminished. When injected into monkeys intracerebrally, it no longer produced a fatal encephalitis but only a moderate febrile reaction, followed by recovery and solid immunity to reinoculation with a highly virulent strain of virus. When injected intracerebrally into mice, the mortality ratio was not diminished but the incubation period was markedly prolonged. 5. The changes in the pathogenicity of the virus cultivated in medium containing testicular tissues were somewhat similar to those observed after cultivation in chick embryo medium which contained only a minimal amount of nervous tissue. Its viscerotropic affinity had been largely lost and only very small amounts of virus were found in the circulating blood of monkeys inoculated subcutaneously. Given intracerebrally, it produced death from encephalitis in monkeys. The incubation period in mice inoculated intracerebrally with this virus was also prolonged but somewhat less so than with the virus grown in chick embryo tissues without the central nervous system.